Smoking Behavior, Demographic Factors and Smoking Cessation Among Rural and Urban Residents - Zekeri, Andrew A. (J Healthc Sci Humanit, 2018)
Smoking remains a leading cause of morbidity and mortality worldwide. Though age and gender differences in smoking in the United States population have been documented, data about these differences and smoking cessation among rural and urban residents is limited. The purpose of the research is to examine the relationship between health status, age, gender and smoking among samples of rural and urban adults. The paper also examined reasons why some respondents quit smoking and who encouraged them to quit. Data for this analysis were obtained by a telephone survey of two samples of adults 30 years of age and older: 150 residents from an urban county and 150 from a rural county in Pennsylvania. Data included information on health status, a number of health behaviors (including smoking cigarettes), age, gender, and smoking cessation. The results indicate that for respondents residing in the rural county, whether a person is a male or female is statistically related to smoking. Age is statistically related to smoking. There is no relationship between health status and smoking. Those who quitted smoking did for health reasons and were more likely to had support from family members (spouse and children). Smoking (smoke now, used to smoke and never smoked) did not relate consistently nor strongly to health status when residence and gender were controlled. Programs promoting smoking cessation might benefit by involving family or other household members.